Therapeutic interventions into innate immune diseases by means of Aptamers - Yasmeen, Farzana; Seo, Hana; Javaid, Nasir; Kim, Moon Suk; Choi, Sangdun (Pharmaceutics, 2020)
The immune system plays a crucial role in the body’s defense system against various pathogens, such as bacteria, viruses, and parasites, as well as recognizes non-self-and selfmolecules. The innate immune system is composed of special receptors known as pattern recognition receptors, which play a crucial role in the identification of pathogen-associated molecular patterns from diverse microorganisms. Any disequilibrium in the activation of a particular pattern recognition receptor leads to various inflammatory, autoimmune, or immunodeficiency diseases. Aptamers are short single-stranded deoxyribonucleic acid or ribonucleic acid molecules, also termed “chemical antibodies,” which have tremendous specificity and affinity for their target molecules. Their features, such as stability, low immunogenicity, ease of manufacturing, and facile screening against a target, make them preferable as therapeutics. Immune-system–targeting aptamers have a great potential as a targeted therapeutic strategy against immune diseases. This review summarizes components of the innate immune system, aptamer production, pharmacokinetic characteristics of aptamers, and aptamers related to innate-immunesystem diseases.
Keywords: Aptamer; Innate immune system; Pattern recognition receptor; Targeted therapy